General Education in the DCCCD [Dallas County Community College District] and Skills for Living Ruth G. Shaw. - Shaw, Ruth G. (Distributed by ERIC Clearinghouse, 1981)
Based upon the efforts of the Dallas County Community College District (DCCCD) to develop a comprehensive set of general education goals and directions, this paper suggests principles for the development of community college general education curricula. While conceding that a core curriculum for general education is an excellent statement of a college's values, the paper first warns against adopting university models for general education which are unsuited for today's nontraditional student. The DCCCD's efforts to involve faculty and community leaders in the identification of essential "Skills for Living" are then described. Finally, five principles that emerged from these efforts are discussed: (1) each college must develop its own goals for general education; (2) staff must be allowed time to become familiar with and committed to these goals; (3) the goals must have community affirmation; (4) faculty commitment to general education is essential; and (5) the goals must be integrated into the institutional planning process. A second report summarizes the underlying assumptions, goals, and specific objectives of DCCCD's "Skills for Living," which provide directional guidelines for developing eight competency areas: living with yourself, others, and the environment; living as a producer, consumer, and in the community; and living creatively and in the future. (JP)